LITERASI KEUANGAN SISWA SEKOLAH DASAR DI KABUPATEN DEMAK - Ilfa, Farah Nur Anina; Sumarni, Woro; Widiarti, Nuni; Sumartiningsih, Sri; Yuwono, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Financial literacy is essential for individuals to navigate the complexities of the 21st century, including challenges like online debt. To equip students with the necessary skills, a comprehensive strategy to enhance financial literacy is required. The initial step in this process is to assess the current state of financial literacy among students. This study aimed to describe the financial literacy levels of elementary school students in the Demak Regency. Data was collected through questionnaires, interviews, and observations, and was analyzed descriptively. The findings revealed that only 52% of the students practiced independent saving habits, indicating a relatively low level of financial literacy. Although these students may be familiar with basic financial products such as savings accounts, their understanding of broader financial management concepts is limited.